Beyond Lactate: Is There a Role for Serum Lactate Measurement in Diagnosing Acute Mesenteric Ischemia? - İhsan Ekin Demir; Güralp O. Ceyhan; Helmut Friess (2012)
Background/Aims: Measurement of serum lactate remains the most frequently applied laboratory investigation to diagnose acute mesenteric (intestinal) ischemia. The present review aims at critically questioning the widespread measurement of serum lactate to diagnose acute mesenteric ischemia in clinical practice and at drawing attention to more novel markers of intestinal ischemia. Methods: An electronic search of multiple databases was performed with the key words ‘lactate’, ‘marker’, ‘mesenteric’, ‘intestinal’ and ‘ischemia’ to detect all relevant studies. Additionally, the references of published articles were also reviewed. Results: Serum lactate is an unspecific marker of tissue hypoperfusion and undergoes significant elevation only after advanced mesenteric damage. While L-lactate is the routinely measured stereoisomer of lactate, the other stereoisomer, D-lactate, has been shown to bear a somewhat higher specificity, which is still not comparable to the extremely specific nature of ischemia markers from other organs (e.g. cardiac ischemia). Larger studies are currently lacking to reliably advocate the routine clinical usage of novel markers like mucosal damage markers such as intestinal fatty acid-binding protein. Conclusion: Based on current evidence, the level of no single serum marker, including serum lactate, is elevated early and specifically enough in the serum to diagnose acute mesenteric ischemia.